Total quality management, employee commitment and competitive advantage in Nigerian tertiary institutions. A study of the University of Lagos - B.O. Abimbola; E.O. Oyatoye; O.G. Oyenuga (International Journal of Production Management and Engineering, 2020)
The quality of education offered by the tertiary institutions in Nigeria in recent times has critically degenerated. Unfortunately, this has led to the unprecedented rise in the poor quality of Nigerian graduates which contributes to the very alarming high rate of unemployment in the country. This article therefore examines the relationship between total quality management (TQM), employee commitment and competitive advantage among tertiary institutions in Lagos State with a particular focus on the University of Lagos, using a survey research design with a random selection of 350 respondents from a population of 2,047 staff strength across the 11 faculties in the university. The data used for this article were derived from a systematic review of the relevant literature and a structured questionnaire. The data obtained from the questionnaire was subjected to descriptive and inferential statistics. The result showed that the adoption of total quality management practices and employee commitment significantly affects competitive advantage. The findings suggest that proper adoption of TQM practices coupled with employee commitment will guarantee competitive advantage outcomes measured in terms of increase in revenue, customer satisfaction and employee satisfaction. TQM and employee commitment through its principles can successfully contribute to enhanced organizational performance and dynamic competitiveness.